The use of technology-assisted intervention in vocabulary learning for children with autism spectrum disorder: a systematic review - Urrea, Ana Lucia; Fernández-Torres, Vanessa; Rodriguez-Ortiz, Isabel R.; Saldaña, David (Frontiers in Psychology, 2024)
Introduction: Children with autism spectrum disorder may show delays in vocabulary development. Technology-based interventions could facilitate the teaching of different vocabulary skills; however, it is still not clear whether technology represents an added value. Methods: The current review preregistered in PROSPERO evaluates the efficacy of technology-based interventions in vocabulary learning for children with autism spectrum disorder. We selected articles published in the period 2006-2022 from five databases. Results: The results identified two group studies, one within subject design, nine single-case studies and one randomized controlled design in participants aged 0 to 16 years who had used technological devices to learn vocabulary. Overall, five of the 13 studies showed positive results of using technology-assisted intervention, six described mixed results, one described negative result, and one described no differences in technology-assisted intervention. The studies are divided into the categories of efficacy of technology and comparison between technology and non-technology. Discussion: In summary, technology, such as tablets and computers, might be useful tools to improve vocabulary skills in certain children with ASD. However, the various degrees of impact found in the studies we reviewed indicate that personalized assessments, acknowledgment of previous experiences, and awareness of the context of usage are essential. The contrast with nontechnological approaches highlights the necessity for more detailed studies to pinpoint the precise conditions under which technology-based interventions can offer the most advantages.